A comparative study showing effect of local insulin injection on wound vascularization seen in color Doppler imaging in patients with diabetic foot ulcer disease before and after therapy - Mayurika Singh; Singh, Saurabh; Singh, Sanjay; Uttam, Sarthak (Asian Journal of Medical Sciences, 2022)
Background: Diabetic foot ulcer disease is one of the most common complications of diabetes, especially in developing nations like India. Management and successful treatment of diabetic ulcers have been under rigorous research and interventions for the past few decades now. This study is an attempt to analyze the effects of a relatively newer treatment modality for diabetic foot ulcers. Aims and Objectives: The primary objective of this study was to determine results after treating patients of diabetic foot ulcers with local insulin injection therapy and compare with the placebo group after 1 week of treatment. Materials and Methods: In this study, 50 patients with diabetic foot ulcer disease were enrolled, of which 25 patients were randomly selected for the intervention group and the rest were kept in a control group. In the intervention group, patients were treated by injecting insulin preparation at the ulcer site whereas in control group, normal saline was used. Wound assessment was done by measuring the ulcer size and by determining the ankle peak systolic velocity (APSV) using color Doppler technique before and after the treatment in both intervention and control groups. Results: Mean ulcer size before the treatment (7.19 cm2) was higher than post-treatment size (3.48 cm2) and the difference was statistically highly significant (P=0.00) while there was no significant difference in ulcer size post-treatment by insulin or non-insulin (normal saline) group (P=0.274). Mean APSV before the treatment (30.75 cm/s) was lower than post-treatment velocity (43.50 cm/s) and the difference was statistically highly significant (P=0.00) while there was no significant difference in APSV post-treatment by insulin or non-insulin (normal saline) group (P=0.061). Conclusion: It meant that insulin and normal saline were equally effective in reducing ulcer size and improving APSV without being superior to one another.